Thioredoxin 1 Enhances Neovascularization and Reduces Ventricular Remodeling During Chronic Myocardial Infarction: A Study Using Thioredoxin 1 Transgenic Mice - Adluri, Ram Sudheer (2010)
Oxidative stress plays a crucial role in disruption of neovascularization by alterations in thioredoxin-1 (Trx1) expression and its interaction with other proteins after myocardial infarction (MI). We previously showed that Trx1 has angiogenic properties, but the possible therapeutic significance of overexpressing Trx1 in chronic MI has not been elucidated. Therefore, we explored the angiogenic and cardioprotective potential of Trx1 in an in vivo MI model using transgenic mice overexpressing Trx1. Wild type (W) and Trx1 transgenic (Trx1(Tg/+)) mice were randomized into W Sham (WS), Trx1(Tg/+) Sham (TS), WMI and TMI. MI was induced by permanent occlusion of LAD coronary artery. Hearts from mice overexpressing Trx1 exhibited reduced fibrosis and oxidative stress, and attenuated cardiomyocyte apoptosis along with increased vessel formation compared to WMI. We found significant inhibition of Trx1 regulating proteins, TXNIP and AKAP 12, and increased p-Akt, p-eNOS and p-GSK-3β, HIF-1α, β-catenin, VEGF, Bcl-2 and survivin expression in TMI compared to WMI. Echocardiography performed 30 days after MI revealed significant improvement in myocardial functions in TMI compared to WMI. Our study identifies a potential role for Trx1 overexpression and its association with its regulatory proteins TXNIP, AKAP12 and subsequent activation of Akt/GSK-3β/β-catenin/HIF-1α-mediated VEGF and eNOS expression in inducing angiogenesis and reduced ventricular remodeling. Hence, Trx1 and other proteins identified in our study may prove to be potential therapeutic targets in the treatment of ischemic heart disease.